TO COMPARE THE EFFICACY OF MYCOPHENOLATEMOFETYL WITH CYCLOPHOSPHAMIDE IN THE MANAGEMENT OF LUPUS NEPHRITIS - Dilshad Muhammad; Khalid Amin; Abid Rashid et al. (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVE: To compare the efficacy of mycophenolatemofetyl with cyclophosphamide in the management of lupus nephritis in local population and compairing the results with studies within aand out of Pakistan. STUDY DESIGN: Comparative study SETTING: All the cases admitted through OPD and emergency in Medical Unit IV of DHQ Hospital Faisalabad. DURATION WITH DATES: From 15-06-2011 to 14-02-2012. SUBJECTS AND METHODS: Seventy two patients meeting the inclusion criteria were included in this study. They were allocated randomly in two groups of 36 patients. Group A, received mycophenolatemofetyl(MMF)orally and group B received intravenous cyclophosphamide(CYC) as monthly pulses of 0.5 g/m2 body surface area. Both groups received prednisolone at a dose of 1mg/kg/day with tapering by 10-20% at one week or two week intervals on the basis of clinical improvement Chi Square test was used to compare the efficacy of two drugs based on remission after 24 weeks. P value of <0.05 was taken as significant. RESULTS: The mean age of the patients in group A was 27.6±5.0 years and in group B was 28.4±4.9 years. In group A, there were 3 (8.3%) male patients and 33 (91.7%) female patients. In group B, there were 36 (100%) female patients. In group A, 9 (25%) patients got remission from the treatment and in group B, 2 (5.6%) patients got remission from the treatment. CONCLUSION: It is concluded from this study that mycophenolatemofetyl(MMF)administered orally is superior in efficacy to intravenous cyclophosphamide(CYC) in the management of lupus nephritis.